2022
DOI: 10.1002/jmri.28463
|View full text |Cite
|
Sign up to set email alerts
|

Advances in The Application and Research of Magnetic Resonance Diffusion Kurtosis Imaging in The Musculoskeletal System

Abstract: Magnetic resonance diffusion kurtosis imaging (DKI) is an emerging magnetic resonance imaging (MRI) technique that can reflect microstructural changes in tissue through non‐Gaussian diffusion of water molecules. Compared to traditional diffusion weighted imaging (DWI), the DKI model has shown greater sensitivity for diagnosis of musculoskeletal diseases and can help formulate more reasonable treatment plans. Moreover, DKI is an important auxiliary examination for evaluation of the motor function of the musculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
(290 reference statements)
0
3
0
2
Order By: Relevance
“…Five-facet mindfulness. We used the Five-Facet Mindfulness Questionnaire (FFMQ), which was compiled by Baer et al (2006) and translated and revised by Deng et al (2019). The scale uses Chinese expressions only for translation and understanding purposes, but it contains the same five dimensions and 39 items for Chinese students.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five-facet mindfulness. We used the Five-Facet Mindfulness Questionnaire (FFMQ), which was compiled by Baer et al (2006) and translated and revised by Deng et al (2019). The scale uses Chinese expressions only for translation and understanding purposes, but it contains the same five dimensions and 39 items for Chinese students.…”
Section: Methodsmentioning
confidence: 99%
“…For those who struggle to maintain focus, the performance gains from positive thinking training are enhanced, and attention becomes more focused, resulting in the suppression of distracting thoughts (Mrazek et al, 2013). A systematic review of fMRI studies on mind-wandering revealed that mind-wandering was a significant predictor of metacognition, and mindfulness uniquely moderated the association between mind-wandering and metacognition (Deng et al, 2019). Research has also found that mindfulness increases the efficiency of attention, which can be significantly improved by reducing thoughts and behaviours which are not relevant to the task at hand (Neubauer & Fink, 2009).…”
Section: The Mediating Role Of Mind-wanderingmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploring the heterogeneity of tumors remains a key focus and challenge in both scientific research and clinical practice. Diffusion kurtosis imaging (DKI) allows a more detailed assessment and response to the microstructural properties of living tissues ( 7 ) and has been implemented in various clinical applications ( 8 , 9 ). DKI can effectively represent the non-Gaussian distribution of water molecule diffusion and quantify deviations from Gaussian diffusion.…”
Section: Introductionmentioning
confidence: 99%